Cast bulk glassy alloys: fabrication, alloy development and properties - Qingsheng Zhang; Chunling Qin; Akihisa Inoue (China Foundry, 2010)
Metallic glasses represent an interesting group of materials as they possess outstanding physical, chemical and mechanical properties compared to their crystalline counterparts. Currently, with well designed compositions it is possible to cast liquid alloys into the glassy state at low critical cooling rates from 100 K•s-1 to 1 K•s-1 and in large critical sample sizes up to several centimeters, which significantly enhances the promise for possible applications as advanced engineering materials. This paper reviews the development of (ZrCu)-based bulk metallic glasses with large sizes by copper mold casting and their unique properties. Additionally, the ex-situ and in-situ second phases reinforced BMG composites with large plasticity are also presented.